Characterisation and assessment of the most popular mobile apps designed for neck pain self‐management: A systematic search in app stores. (12th August 2021) - Marques, Joana; Borges, Lauta; Andias, Rosa; Silva, Anabela G.
Abstract: Purpose: This study aimed to assess commonly downloaded apps targeting neck pain (NP) using the Mobile Apps Rating Scale (MARS), to characterise the interventions described in the apps and to correlate the ratings of quality retrieved from app stores against the ratings of quality assessed using MARS. Materials and methods: A systematic search was conducted at the Apple App Store, Google Play, Windows Phone Store and Huawei App Gallery. Mobile apps with 100 or more ratings, a user rating of 4 or higher and which were available for free were retrieved for assessment. Results: A total of 17 apps met the inclusion criteria. The mean user rating was 4.4 ± 0.28, the mean MARS score was 4.0 ± 0.58 and the correlation between user ratings and MARS total scores and subdomains varied between a maximum of 0.41 ( p > 0.05) and a minimum of −0.11 ( p > 0.05). All apps included exercise but only 5 (29%) included an educational component. Conclusions: The most downloaded apps on NP available for free in app stores are, generally, of acceptable quality as assessed by the MARS total score, target exercise, but fail to include an appropriate educational component. The user rating available in app stores is not an indicator of the quality of the apps. Therefore, health professionals should carefully assess the mobile apps before recommending them to the patients.